Lenin’s Void: Towards a Kenogrammar of Management - Baecker, Dirk (MAD, 2013)
There is no general accepted sociology of management and the cognitive approach of sociology itself has difficulties to deal with volitive aspects of management. This paper presents an attempt to understand management as an evolutionary mechanism which integrates both cognitive and volitive aspects. The general idea of a Kenogramatik is introduced, which helps describing the void processed for management introducing an objective. Next section presents a model which describe management of Russian revolution of Lenin as an ¨strategy of access" (Philip Selznick). The Bolchevism transforms members of the Party into agents, who try to put themselves in different relevant organizations and they are supported in this process with, both an adequate "theory" and by a certain routine "praxis" of the revolution itself.